Field evaluation and break-even analysis of specialty soybeans for biodiesel and meal protein production. Issue 1 (2nd January 2018) - Stobaugh, Bryan; Chen, Pengyin; Jaureguy, Luciano M; Florez-Palacios, Liliana; Orazaly, Moldir; Zeng, Ailan
ABSTRACT: The economic value of a soybean [Glycine max (L.) Merr.] crop depends on yield and quality. The objectives of this study were to evaluate soybean lines for protein and oil content and to examine the break-even (BE) analysis of these traits combined with yield. Forty lines of maturity group (MG) IV or V were grown at four Arkansas locations for two years. Yield, protein, and oil content of each line were determined and compared to the check average for a BE comparison of the total economic value of the line. Results showed six profitable lines (8.40 to 54.96 per metric ton based on yield) in 2008 and six profitable lines (0.49 to 61.19 per metric ton based on yield) in 2009. Overall, in both MG, high-protein lines needed to yield more to be profitable, whereas high-oil lines had competitive yield, protein and oil content; R00-764 (MG IV), R05-71 (MG V), and R02-6185F (MG V) were competitive without added premiums.